On the pointwise multiplication in Besov and Lizorkin-Triebel spaces - Douadi Drihem; Madani Moussai (International Journal of Mathematics and Mathematical Sciences)
Under some sufficient conditions satisfied by F-space of Lizorkin and Triebel and B-space of Besov, we prove some embeddings of types F⋅B↪F, F⋅F↪F, and B⋅B↪B.